2017
DOI: 10.1371/journal.pone.0177766
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen therapy for wound healing in diabetic rats: Varying efficacy after a clinically-based protocol

Abstract: Hyperbaric oxygen therapy (HBOT) is a clinical treatment in which a patient breathes pure oxygen for a limited period of time at an increased pressure. Although this therapy has been used for decades to assist wound healing, its efficacy for many conditions is unproven and its mechanism of action is not yet fully clarified. This study investigated the effects of HBOT on wound healing using a diabetes-impaired pressure ulcer rat model. Seven weeks after streptozotocin-induced diabetes in rats (n = 55), a pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Professional sports teams have also favored the use of HBOT to speed injury ( Strauss et al, 1983 ; Strauss and Hart, 1984 ; Skyhar et al, 1986 ; Cianci and Sato, 1994 ; Goldfarb et al, 2016 ). Moreover, several studies have proposed that HBOT mobilizes stem cells by improving homing and subsequent engraftment in injured tissues, which would explain, in part, the therapeutic effects of HBOT ( Zádori et al, 2011 ; van Neck et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Professional sports teams have also favored the use of HBOT to speed injury ( Strauss et al, 1983 ; Strauss and Hart, 1984 ; Skyhar et al, 1986 ; Cianci and Sato, 1994 ; Goldfarb et al, 2016 ). Moreover, several studies have proposed that HBOT mobilizes stem cells by improving homing and subsequent engraftment in injured tissues, which would explain, in part, the therapeutic effects of HBOT ( Zádori et al, 2011 ; van Neck et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also blood flow in the micro circulation showed a significant increase on days 17, 21 and 31 but a significant decrease on days 24 and 28. Inflammation scoring showed significantly decreased CD68 counts in the HBOT group on day 42, but not in the early stages of wound healing (28).…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies revealed that vibration and hyperbaric oxygen therapies remarkably improve muscle ischemia and attenuate ulceration after severe pressure loading. 15,43 Therefore, the application of both therapies should be preferentially considered to prevent the occurrence or deterioration of deep PIs in patients with the CT + TT genotype of HIF1A rs11549465.…”
Section: Discussionmentioning
confidence: 99%